Eyelid Malposition Repair: A Review of the Literature and Current Techniques - Guthrie, Ashley J.; Kadakia, Pooja; Rosenberg, Joshua (Seminars in Plastic Surgery, 2019)
Eyelid malposition is a challenging problem faced by surgeons. Given the delicate nature of the eyelid and its complex anatomy, eyelid repair requires both a comprehensive understanding of eyelid anatomy along with thorough presurgical planning and surgical execution. A wide range of options is available for eyelid reconstruction but the location and extent of the deformity often dictate the type of repair. This article is a review of commonly encountered forms of eyelid malposition. Relevant reconstructive techniques and current evidence-based methods of reconstruction are discussed in detail. Anatomical considerations, the nature of specific defects, pearls of preoperative evaluation, and the reconstructive options available to the facial plastic and oculoplastic surgeon are outlined. Topics discussed include ectropion, entropion, eyelid retraction, and blepharoptosis.
Keywords: eyelid malposition; ectropion; entropion; retraction; blepharoptosis